5x - 8a + 4a - 2x + a

Here, all you have to do is combine like terms:

5x - 8a + 4a - 2x + a ===> 5x - 2x - 8a + 4a + a ===> 3x - 3a

Thus, your answer is: 3x - 3a **OR** 3(x - a)

5x - 8a + 4a - 2x + a

Tutors, please sign in to answer this question.

Here, all you have to do is combine like terms:

5x - 8a + 4a - 2x + a ===> 5x - 2x - 8a + 4a + a ===> 3x - 3a

Thus, your answer is: 3x - 3a **OR** 3(x - a)

5x-8a+4a-2x+a

I start by underlining the corresponding letters, then combining.

-8a+4a=-4a

-4a+a=-3a Done with A's

Now 5x-2x=3x done with x's so that leaves you with 3x-3a

So

Richard M.

Experienced tutor and lifelong learner

New York, NY

Amy M.

Statistics Tutor Specializing in Real World Applications

Montclair, NJ

4.9
(23 ratings)